Digging deep into a GAC filter – Temporal and spatial profiling of adsorbed organic micropollutants. (30th June 2022) - Edefell, Ellen; Svahn, Ola; Falås, Per; Bengtsson, Elina; Axelsson, Michael; Ullman, Regine; Cimbritz, Michael
Highlights: Extraction of micropollutants at varying depths of an activated carbon filter. Progression of the adsorption front for various micropollutants. Lower adsorption affinity implies faster progression of the adsorption front. Adsorption in bottom layer of GAC filter correlates with lower removal efficiencies. Mass estimations indicated biodegradation for certain micropollutants in the filter. Abstract: A large pilot-scale granular activated carbon (GAC) filter was operated downstream in a full-scale wastewater treatment plant to remove organic micropollutants. To describe the spatial and temporal developments of micropollutant adsorption profiles in the GAC filter, micropollutants were extracted from GAC media taken at various filter depths and number of treated bed volumes. At a low number of treated bed volumes (2600 BVs), most micropollutants were adsorbed in the top layers of the filter. At increasing number of treated bed volumes (7300–15, 500 BVs), the adsorption front for micropollutants progressed through the filter bed at varying rates, with sulfamethoxazole, fluconazole, and PFOS reaching the bottom layer before carbamazepine and other well-adsorbing micropollutants, such as propranolol and citalopram. Higher amounts of adsorbed micropollutants in the bottom layer of the filter bed resulted in decreased removal efficiencies in the treated wastewater. Mass estimations indicated biodegradation for certain micropollutants, such as naproxen, diclofenac, and sulfamethoxazole. A temporary increase in the concentration of the insecticide imidacloprid could be detected in the filter indicating that extraction of adsorbed micropollutants could provide an opportunity for backtracking of loading patterns. Graphical abstract: Image, graphical abstract